Is leadership motivation affected by career orientation? A case study of Malaysian youth in public universities - Tiraieyari, Neda; Abdul Hamid, Jamaliah; Omar, Zoharah; Wahat, Wahiza; Othman, Jamilah; De Silva, Jeffrey Lawrence (Canadian Center of Science and Education, 2014)
This paper aim to determine the relationship between career orientations and leadership motivation among Malaysian youth. Data were collected from 711 undergraduate students from five Malaysian public universities. Results showed that some career anchors correlated significantly with motivation to lead (MTL) with correlation coefficients ranging from 0.1 to 0.4. Results of Regression analysis revealed that the General Management career anchor is the biggest predictor of MTL followed by Pure Challenge. The findings suggest that not all the career anchors contribute significantly in explaining the variation of MTL. Based on R2 value, the career orientations explain about 27.9% of the variance in the MTL. The findings from this study could help policy makers in developing youth career program.